Pembinaan Disiplin Pola Semi Militer dan Keagamaan dalam Sistem Boarding School di SMA Terpadu Wirabhakti Gorontalo - Najamuddin Petta Solong; Ismail Busa (Pascasarjana IAIN Sultan Amai Gorontalo, 2020)
This research aims to analyze the discipline fostering of semi-military and religious patterns in the boarding school system at SMA Terpadu Wirabhakti Gorontalo. The research is qualitative which used the phenomenology approach. The research results showed that discipline fostering usually refers to following student life rules (Perdupsis) and school vision and mission. A Semi-military discipline adopts not only the attributes and participation of TNI (Indonesian National Armed Forces) and Brimob, particularly during the New Student Orientation but disciplinary behavior in dormitory life and the nature of state defense education. As for fostering religious discipline by adopting the Pesantren education system therefore this school is also known as the Islamic Boarding School by accustoming to the discipline of worship, particularly prayer in the congregation, providing rewards and punishment with different treatment as a religious motivation and providing material in Islamic studies in mosques.